The Analytical Framework of Governance in Health Policies in the Face of Health Emergencies: A Systematic Review - Díaz-Castro, Lina; Ramírez-Rojas, María Guadalupe; Cabello-Rangel, Héctor; Sánchez-Osorio, Ever; Velázquez-Posada, Mauricio (Frontiers in Public Health, 2022)
The Governance Analytical Framework (MAG) defines governance as a social fact, endowed with analyzable and interpretable characteristics, through what it calls observable constitutive elements of governance: the problem, the actors, the social norms, the process of decision-making and scope or nodal points; in the sense that each society develops its modes of governance, its decision-making or conflict resolution systems among its members, its norms, and institutions. In this perspective, the purpose of this article was to carry out a systematic review of the scientific literature to understand the role of governance in health policies in health emergencies, such as that caused by the SARS-CoV-2. The systematic review was designed based on the methodology proposed in the PRISMA (Preferred Reporting Items for Systematic Review and Meta-Analysis) Declaration. The literature search was carried out in six databases: Psychology and Behavioral Sciences, APA-PsycInfo, MEDLINE, eBook Collection (EBSCOhost), PubMED, and MedicLatina, published in the last 5 years. Fifteen articles that met quality and evidence criteria were analyzed. The governance approach alluding to the health emergency problem in health policies was the most addressed by the authors (80%), followed by a description of the actors (40%), the process of decision-making spaces (33%), and ultimately, social norms or rules with 13%. Formulating a coherent set of global health policies within a large-scale global governance framework is mostly absent. Although the countries adopt international approaches, it is a process differentiated by the social, economic, and political contexts between countries, affecting heterogeneous health outcomes over the pandemic.